Analysis Of Employee Engagement In Kendang Jimbe Industry, Blitar City - Zuli, Mohammad Dullah; Sudarmiatin, Sudarmiatin; Bidin , Rosmiza (International Journal of Science, Technology & Management, 2022)
The human resources which have reliable and productive have an important role for organizations or companies, especially in the era of 4.0 and digitalization in the business world, especially in employee engagement, where employees are the spearhead of the company. This study aims to see how Employee Engagement in the Kendang Jimbe Blitar Industry. This study use a qualitative descriptive research method. The results of the research from the human resource side show that CV Cherry Blossom Indonesia is very qualified because of the many employees who work all are experts (professionals), but this is a weak point for similar SMEs, especially the Kendang Jimbe Industry because after all these experts will very prone to come out if there is something that might not make them comfortable being there. 2. In terms of Employee Engagement a) Vigor : the policy which have done by the management (Mrs. Anik Sriati) to rest their employees during the day is an aspiration from the employee's proposal, of course this has been recieved so that during effective hours they can carry out activities optimally. 2) Dedication is a strong relationship between workers and what they do. CV Cherry Blossom Indonesia with 40 employees has a strong dedication to their work, this happens because indeed Kendang Jimbe Craft is a series of activities that can be carried out by experts, so that the Kendang Jimbe Industry employees there are very dedicated. 3) Absoption: work activities in the Kendang Jimbe Industry often exceed the time limit determined by the management. Sometimes workers can stay up at night while doing their work, this is certainly a note for management because after all, all work must be assessed properly.